Edukasi Ilmu Kebumian Dan Potensi Kebencanaan Geologi Bagi Siswa SMA Negeri 1 Sarjo - Janat, Nunik Rezkiarti; Fitriana, Tati; Asrafil, Asrafil; Mukaddas, Abdul; Nugroho Uno, Djamal Adi; Mulyati, Sri (Universitas Negeri Gorontalo, 2025)
Considering the geological complexity of Sulawesi and the limited exposure of students to basic geoscience knowledge in formal education, SMA Negeri 1 Sarjo, located in West Sulawesi and bordering Central Sulawesi, recognized the need to conduct a knowledge-sharing activity on earth science, geological resources, and geological hazards. This program invited academic experts from the Faculty of Engineering, Universitas Tadulako, to deliver educational materials tailored for high school students. The main objective was to enhance students’ understanding of geoscience concepts, introduce the diversity of geological resources, and increase awareness of geological hazards, particularly those prevalent in Sulawesi. The activity involved grade XII students through presentations, discussions, and interactive question-and-answer sessions. Students and teachers responded positively, indicating increased interest and comprehension of the topics presented. The positive feedback and appreciation expressed by the school, especially through the Vice Principal for Curriculum and Student Affairs, served as an indicator of the program’s success.